Impacts of Cytochrome P450 2D6 (CYP2D6) Genetic Polymorphism in Tamoxifen Therapy for Breast Cancer - Bezerra, Lucas Soares; Santos-Veloso, Marcelo Antônio Oliveira; Bezerra Junior, Natanael da Silva; Fonseca, Lucilia Carvalho da; Sales, Wivianne Lisley Andrade (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Tamoxifen (TMX) is the main drug used both in pre and postmenopausal women as adjuvant treatment for hormone receptor-positive breast cancer. An important barrier to the use of TMX is the development of drug resistance caused by molecular processes related to genetic and epigenetic mechanisms, such as the actions of cytochrome P450 2D6 (CYP2D6) polymorphisms and of its metabolites. The present study aimed to review recent findings related to the impact of CYP2D6 polymorphisms and how they can affect the results of TMX in breast cancer treatment. The keywords CYP2D6, tamoxifen, and breast cancer were searched in the PubMed, Scopus, The Cochrane Library, Scielo, and Bireme databases. Studies related to other types of neoplasms or based on other isoenzymes from cytochrome P450, but not on CYP2D6, were excluded. The impact of CYP2D6 polymorphisms in the TMX resistance mechanism remains unclear. The CYP2D6 gene seems to contribute to decreasing the efficacy of TMX, while the main mechanism responsible for therapy failure, morbidity, and mortality is the progression of the disease.
Keywords: cytochrome P-450 CYP2D6; polymorphism genetic; tamoxifen; breast neoplasms; therapeutic uses